AIR BAGI RITUAL ADAT DI DUSUN TUTUP NGISOR DALAM FOTOGRAFI 3D ANAGLYPH - Kusuma, Sigit Setya (Universitas Swadaya Gunung Jati, 2024)
This research is aimed at visualizing water in Tutup Ngisor village that is specifically used for traditional rituals in 3D anaglyph photography. A qualitative study by observation, Tutup Ngisor community figures interview, and a literature study was done in collecting the data. The result from those processes can be concluded that apart from agricultural and household needs, Tutup Ngisor has water guarded in such a way and originates from more than 144 water springs. The water is made through a long process of prayers and meditation and is also used and utilized for ritual purposes, treatment, and community special needs. Based on those facts, two 3D anaglyph photography artworks are made, which portray the process of creating water for traditional rituals in Tutup Ngisor village. Keywords: Traditional rituals, water, Tutup Ngisor village